Um estudo sobre a recriação do mito em O pássaro do sol, de Myriam Fraga - Passos, Jeane da Silva (2018)
This dissertation has as main objective to present a study about the re-creation of the myth in the book The bird of the Sun (2010), of the Bahian writer Myriam Castro de Lima Fraga (1937-2016), she is known as Myriam Fraga. This literary work deals with an indigenous tale and narrates, from the memory of an old woman, presented by the storyteller, the emergence of the fire. This narrative links the times, symbolizing not only the present time, but also joining the mythological reality, from the re-creation and appropriation of a myth. The text under study reveals the connection of the times: past and present united to individual and collective memory. This dissertation intends to answer the following central problematic: Why does it bring the story of the myth of the one who stole the fire? This questioning also unfolds in the following problem: What choices are made by the writer in re-reading this myth? For this, the present work is divided in two parts. The first part proposes a strictly theoretical discussion about the figure of the storyteller, concepts, positions and transformations which this figure has suffered through the ages. The storyteller’s memory composes the narrative of The bird of the sun and symbolizes the individual and collective memory in the contemporary scope. In the second part, we deepen in our reading on the book The bird of the sun, with the focus turned to the mythical recreation. To support this analysis, we used the studies of Roque de Barros Laraia (1970), Mircea Eliade (1972), Maria Lúcia Dal Farra (1978), Junito de Souza Brandão (1986), Jean PierreVernant (1990), Walter Benjamin (1994), Henri Bergson (1999), Cristina Pompa (2003), Júlio Cezar Mellati (2007) and Thomas Bulfinch (2013).